Pengendalian Bahan Baku Pembuatan Produk Cigarette Paper Menggunakan Metode EOQ (Studi Kasus: Pada PT XYZ) - Adi, Muhammad Adi Fatwa; Sari, Rianita Puspa; Yuliandi, Fidy Febryan Muthfy (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Raw material inventory is a significant aspect in the industry, especially in PT XYZ company where there is a problem of excess inventory, regardless of the number of purchases per order. If the inventory of raw materials is too large, it will increase maintenance costs and storage costs in the warehouse. our abstract must be written in a single paragraph and typed in single space. The EOQ method is used in raw material control to determine the quantity of supply orders to minimize storage costs and supply order costs, minimize out of stock so as to save inventory costs incurred in making cigarette paper to be more efficient, and determine the optimal total inventory cost (TIC) in the company. The results of the proposal obtained by calculation using the Economic Order Quantity (EOQ) method are for cigarette paper raw materials in the form of pulp using the EOQ method calculation of 1,054,947.38 kg with a frequency of 3 orders, and Chemical raw materials of 193,939.39 kg with a frequency of 3 orders.